Islam-oriented parties' ideologies and political communication in the quest for power in Morocco the PJD as a case study - Bouyahya, Driss (Cambridge Scholars Publishing, 2015)
The twentieth century saw the rapid rise of groups of Muslims who use Islam as an ideological weapon for their political ends. This is commonly referred to in scholarly and media writings as Islamism, and its proponents are designated as `Islamists', not Muslims, in order to stress that they are attributing an ideological dimension to Islam.